2013
DOI: 10.1371/journal.pone.0082521
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Instruments for Assessing Perinatal Depression in African Settings: Systematic Review and Meta-Analysis

Abstract: Background: A major barrier to improving perinatal mental health in Africa is the lack of locally validated tools for identifying probable cases of perinatal depression or for measuring changes in depression symptom severity. We systematically reviewed the evidence on the reliability and validity of instruments to assess perinatal depression in African settings. Methods and Findings:Of 1,027 records identified through searching 7 electronic databases, we reviewed 126 fulltext reports. We included 25 unique stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 83 publications
4
128
0
Order By: Relevance
“…Among Xhosa-speaking women, several studies have supported the construct validity, criterion-related validity, and factor structure of the EPDS-10 (De Bruin et al 2004; Hartley et al 2011; Lawrie et al 1998), and it has also been shown to have a high sensitivity for detecting postnatal depression in numerous other settings worldwide (Tsai et al 2013). Similar to Kabir et al (2008) and Rochat et al (2013), we defined 4 short and ultra-short versions of the EPDS-10: the 2-item analogue of the Patient Health Questionnaire (EPDS-2) (Lowe et al 2005; Monahan et al 2009), the 3-item anxiety subscale (EPDS-3), an abbreviated 5-item version of the depressive symptoms subscale (EPDS-5) (Rochat et al 2013), and the 7-item depressive symptoms subscale (EPDS-7) (Box 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Xhosa-speaking women, several studies have supported the construct validity, criterion-related validity, and factor structure of the EPDS-10 (De Bruin et al 2004; Hartley et al 2011; Lawrie et al 1998), and it has also been shown to have a high sensitivity for detecting postnatal depression in numerous other settings worldwide (Tsai et al 2013). Similar to Kabir et al (2008) and Rochat et al (2013), we defined 4 short and ultra-short versions of the EPDS-10: the 2-item analogue of the Patient Health Questionnaire (EPDS-2) (Lowe et al 2005; Monahan et al 2009), the 3-item anxiety subscale (EPDS-3), an abbreviated 5-item version of the depressive symptoms subscale (EPDS-5) (Rochat et al 2013), and the 7-item depressive symptoms subscale (EPDS-7) (Box 1).…”
Section: Methodsmentioning
confidence: 99%
“…Accurate screening for, and subsequent diagnosis of, perinatal depression will be an essential component of any strategy to funnel patients to appropriate treatments at scale. Short and ultra-short screening instruments -- defined as having 5-14 items and <5 items, respectively (Mitchell and Coyne 2007) -- for perinatal depression have been studied and validated in several sub-Saharan African countries (Tsai et al 2013). Given their brevity, it is possible that these screening instruments may be efficiently incorporated into the routine workflow of overburdened health care workers.…”
Section: Introductionmentioning
confidence: 99%
“…Further exploration regarding adolescent access to health information surprisingly reveals that students mainly refer to their teachers especially for the problems of reproductive organs. This new technology potentially becomes a new method that might be useful for disseminating health information as long as users are cautious with the credibility and the reliability of the information (Tsai, 2013).…”
Section: The Influence Of Family Support Toward Behaviors In the Treamentioning
confidence: 99%
“…It has also been validated globally, though there is some concern in the effective translation of the EPDS into local languages (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…Another systematic review, a Meta-Analysis, assessed the reliability and validity of EPDS in African settings (29). There was a pooled sensitivity of 0.94 …”
Section: Edinburgh Postnatal Depression Scale (Epds)mentioning
confidence: 99%